PERENCANAAN KAWASAN PERMUKIMAN TEPI SUNGAI CODE PUSAT KOTA YOGYAKARTA - , ANNISA ABDILLAH MUTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The settlement of Code river side that placed in the central of Yogyakarta City is a district located in the east of Malioboro CBD. The density in this district more and more rising because of higher urbanization flow entrance to Yogyakarta City. Many immigrants or newcomers working at CBD arround Malioboro choose to live here. Consequently, growing some unlisenced houses in banks of Sungai Code which in slum condition. Beside that, environment quality of that villages more and more decreasing. To solve that problem, this plan concept has drafted with some purposes in relationship to increasing the quantity of appropriate housing and ease of acces for pedestrian and cyclist. Based from image of the city theory defined by Lynch (1960). The plan also reach of the district elements that expected to improvable the image of dirty district. This concept made based of the data from secondary sources, field surveys, and informant interviews. Moreover, the analysis has done to planning district components (Shirvani) for identify the potential and problems of the district. The potential and problems of the district identified based on Tri Daya approach. The planning concept that suitable with the field characteristics and social condition of citizens is humanism concept. Remembering the limit number of the land, to increase the quantity of appropriate housing doing by applying vertical housing technology. In the other hand, the facts show absence in budget, time, and energy. Furthermore, it needs a priority scale of this plan. Moreover, the core district planning determined to be the major priority of improvement district plan. Base on the data, the plan are : a. Rusunawa with handicraft gallery and watershed park added b. Pedestrian and bicycle bridge c. Rusunami d. Green streescape for river side e. Signage and lighting the river side The last section in this report showing the result of the plan that containing the change of the disctrict elements. Finally, this session also show the catalytic impact from the plan of pedestrian and bicycle bridge that the prior plan in this document.